Margaritaria nobilis L.f. (Phyllanthaceae) Ethanolic Extract: Low Acute Oral Toxicity and Antinociceptive Activity - Fabiana Menezes S. Camara; Brenda Costa da Conceição; Eloise Karoline S. Cardoso; Johan Carlos C. Santiago; Carlos Alberto B. Albuquerque; Washington L. Pereira; Marta C. Monteiro; Consuelo Y. Yoshioka e Silva; Milton Nascimento da Silva; Cristiane F. Maia; Eneas A. Fontes-Junior (MDPI AG, 2023)
Margaritaria nobilis L.f. (Phyllanthaceae), a native Brazilian tree occurring mainly in the Amazon, is used in folk medicine for the treatment of abscesses (bark) and cancer-like symptoms (leaves). The present study evaluates the safety of its acute oral administration and its effects on nociception and plasma leakage. The chemical constitution of the leaf's ethanolic extract is determined by ultra-performance liquid chromatography-high-resolution mass spectrometry (LC-MS. Its acute oral toxicity is evaluated in female rats at a dose of 2000 mg/kg, evaluating the occurrence of deaths and Hippocratic, behavioral, hematological, biochemical, and histopathological changes, as well as food and water consumption and weight gain. Antinociceptive activity is evaluated in male mice with acetic-acid-induced peritonitis (APT) and formalin (FT) tests. An open field (OF) test is performed to verify possible interferences in the animals' consciousness or locomotion. LC-MS analysis shows the presence of 44 compounds classified as phenolic acid derivatives, flavonoids and O-glycosylated derivatives, and hydrolyzable tannins. No deaths or significant behavioral, histological, or biochemical changes are observed in the toxicity assessment. In nociception tests, M. nobilis extract significantly reduces abdominal contortions in APT, demonstrating selectivity for inflammatory components (FT second phase), not interfering in neuropathic components (FT first phase) or consciousness and locomotion levels in OF. Additionally, M. nobilis extract inhibits plasma acetic-acid-induced leakage. These data demonstrate the low toxicity of M. nobilis ethanolic extract, as well as its effectiveness in modulating inflammatory nociception and plasma leakage, possibly related to the flavonoids and tannins present in its composition.